Model of physical training for future specialists of thecustoms service - Mironova, O.V.; Sharonova, A.V.; Yarchikovskaya, L.V.; Ustinova, O.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the model of physical training of future customs service specialists using elements of fitness programs with an emphasis on the development of professionally important physical qualities, increasing mental performance and psycho-emotional state. Methods and structure of the study. As part of solving the research problems throughout the entire period of study (from 2016 to 2021), an analysis was made of the dynamics of the level of physical fitness, mental performance and psycho- emotional state of 50 students of the Bobkov Saint Petersburg branch of Russian Customs Academy. Results and conclusions. As a result of the experiment, a model of physical training of future specialists of the Federal Customs Service of the Russian Federation was developed and tested. The model combines the organizational and pedagogical conditions for its effective functioning, the levels of adaptation to professional activities and directly the means of physical culture, chosen taking into account the professiogram for classes with students of the experimental group. The effectiveness of the developed model is confirmed not only by the data on the increase in the level of physical fitness and the level of psycho- emotional state, but also by the percentage of graduates who remained in the profession.